Autologous serum eyedrops for dry eyes and epithelial defects: clinical and in vitro toxicity studies. Issue 10 (1st October 2001) - Poon, Alexander C; Geerling, Gerd; Dart, John K G; Fraenkel, Graham E; Daniels, Julie T
Abstract : BACKGROUND/AIMS: Autologous serum drops have been reported to be beneficial in keratoconjunctivitis sicca (KCS) and persistent epithelial defects (PED). A clinical pilot study was carried out to examine these potential uses and in vitro toxicity testing on corneal epithelial cell cultures was performed to compare the effect of serum drops with unpreserved hypromellose (hydroxypropylmethylcellulose 0.3%). METHODS: Patients with KCS and PED, unresponsive to conventional treatment were recruited. Patients were examined before treatment, at 1 and 2 weeks after initiation, and then 2 weekly until treatment ceased. Symptoms were assessed at each visit. Clinical examination included Schirmer's test without anaesthesia, rose bengal staining, and fluorescein staining. Epithelial defects were measured with the slit beam. In the laboratory, cultured human corneal epithelial cells were exposed to serum drops and hypromellose, and their viability evaluated with fluorescent viability staining (Calcein AM ethidium homodimer) and an ATP assay. RESULTS: Autologous serum was used in 15 eyes of 13 patients with PED and 11 eyes of nine patients with KCS. In two patients serum drops were started after penetrating keratoplasty (PK). The PKs were performed for perforations secondary to PEDs. Of the 15 eyes with PED, nine healed at a mean of 29 days and six failed. The mean duration of PED before the use of serum drops was 48.2 days. Of the 11 eyes with KCS, six had improved subjective scores and fluorescein scores, and five had improved rose bengal scores after the use of serum drops. For the two patients who used serum eyedrops post-PK, there was a stable and intact epithelium at 1 week. Cessation of serum drops during the postoperative period led to deterioration in the subjective and objective scores in both patients. One developed a PED that responded to reinstitution of serum drops. The morphology and ATP levels of cultured epithelial cells exposed to serum were better maintained than those exposed to hypromellose. CONCLUSION: Autologous serum drops are useful for PED and KCS. This effect may be related to a number of active factors in serum including growth factors, fibronectin, vitamin A, and anti-proteases. In vitro toxicity testing demonstrated that serum drops have reduced toxicity compared with unpreserved hypromellose. Currently regulatory restrictions in the UK have prevented the establishment of a prospective randomised controlled trial examining the efficacy of autologous serum drops for the management of this group of ocular surface disorders.